Parametric Study of Hydrodynamic Coefficients for Circular Cylinders at Subcritical Reynolds Number - Al-Yacouby, A.M. (Springer, 2020)
Vortex induced vibrations of circular structures are well known phenomena in many fields of engineering applications. Up to now, most of the experimental investigations are conducted at low Reynolds Numbers. In this study, the hydrodynamic forces and flow around smooth circular cylinders at subcritical Reynolds (Re) Number was investigated experimentally in the wave basin. The objective of this study is to conduct a parametric study and determine the important parameters affecting drag coefficient (CD) and lift coefficient (CL). The model tests were conducted in the offshore engineering laboratory at Universiti Teknologi PETRONAS (UTP), Malaysia, using rigid vertical cylinders with various outer diameter Do = 27, 34, 42 and 48Â mm. The range of Re Number achieved in the wave basin varied from 3.19E+03 to 2.83E+04 which covers the subcritical flow regime. Generally, the values of CD determined experimentally varied between 1.12 and 1.23, while the values of CL varied between 0.23 and 0.36. The range of these force coefficients are comparable with the recommended values of drag and lift coefficients available in the literature for the similar flow regime. Â© 2020, Springer Nature Singapore Pte Ltd.